Nursing informatics entry to practice competencies: what does it mean for nursing education and practice? - Neumeier, Melanie (My University, 2016)
Discussion of tools that support the integration of digital health content into nursing education. From the Trends and Issues in Nursing Informatics Column.
Keywords: competencies; information; communication; technology; nursing; postsecondary education